Hepatocellular Carcinoma Masquerading as a Large Renal Mass with Hepatic Invasion. (2010) - Zabell, Joseph R. N.; Nepple, Kenneth G.; Wilkinson, Neal W.; Dahmoush, Laila; Williams, Richard D.
Abstract : Large masses are evaluated with imaging to assess primary origin and tumor spread. We present the unusual case of a 53-year-old male with a 17-cm right upper quadrant mass suspected to be renal or adrenal in origin based on radiographic findings. After surgical excision, the mass was subsequently discovered to be primary hepatocellular carcinoma with direct extension to the kidney and adrenal gland. A diagnosis of chronic hepatitis B was made postoperatively. Primary hepatocellular carcinoma with direct renal extension is an exceedingly rare occurrence based on our experience and review of the published literature.